Maternal gender discrimination and child emotional and behavioural problems: A population-based, longitudinal cohort study in the Czech Republic - Stepanikova, Irena; Acharya, Sanjeev; Colón-López, Alejandra; Abdalla, Safa; Klanova, Jana; Darmstadt, Gary L. (EClinicalMedicine, 2022)
Gender discrimination may be a novel mechanism through which gender inequality negatively affects the health of women and girls. We investigated whether children's mental health varied with maternal exposure to perceived gender discrimination. Complete longitudinal data was available on 2,567 mother-child dyads who were enrolled between March 1, 1991 and June 30, 1992 in the European Longitudinal Cohort Study of Pregnancy and Childhood-Czech cohort and were surveyed at multiple time points between pregnancy and child age up to 15 years. The Strengths and Difficulties Questionnaire (SDQ) was administered at child age 7, 11, and 15 years to assess child emotional/behavioural difficulties. Perceived gender discrimination was self-reported in mid-pregnancy and child age 7 and 11 years. Multilevel mixed-effects linear regression of SDQ scores were estimated. Mediation was tested using structural equation models. Perceived gender discrimination, reported by 11.2% of mothers in mid-pregnancy, was related to increased emotional/behavioural difficulties among children in bivariate analysis (slope = 0.24 [95% confidence interval (CI): 0.15, 0.32], p<0.0001) and in the fully adjusted model (slope = 0.18 [95% CI: 0.09, 0.27], p<0.0001). Increased difficulties were evident among children of mothers with more depressive symptoms (slope = 0.04 [95% CI: 0.03, 0.05], p<0.0001), boys (slope = 0.26 [95% CI: 0.19, 0.34], p<0.0001), first children (slope = 0.16 [95% CI: 0.09, 0.23], p<0.0001), and families under financial hardship (slope = 0.09 [95% CI: 0.04, 0.14], p<0.0001). Effects were attenuated for married mothers (slope-0.12 [95% CI: -0.22, -0.01], p<0.05]. Maternal depressive symptoms and financial hardship mediated about 37% and 13%, respectively, of the total effect of perceived gender discrimination on SDQ scores. Perceived gender discrimination among child-bearing women in family contexts was associated with more mental health problems among their children and adolescents, extending prior research showing associations with maternal mental health problems. Maternal depressive symptoms and, to a lesser extent, financial hardship both partially mediated the positive relationship between perceived gender discrimination and child emotional/behavioural problems. This should be taken into consideration when measuring the societal burden of gender inequality and gender-based discrimination. Moreover, gender-based discrimination affects more than one gender and more than one generation, extending to boys in the household even moreso than girls, highlighting that gender discrimination is everyone's issue. Further research is required on the intergenerational mechanisms whereby gender discrimination may lead to maternal and child mental health consequences. Bill and Melinda Gates Foundation; Ministry of Education, Youth and Sports, Czech Republic and European Structural and Investment Funds.